The Search for Spiritual and Self-Identity of the Main Character in the Novel Are You There God? It’s Me, Margaret by Judy Blume - Aprilia Rahmawati; Ujang Suyatman; Dian Nurrachman (Hasanuddin University, 2025)
The search for identity is commonly experienced in adolescent development and includes various aspects such as spirituality and the self. However, in this process, an individual might struggle to adjust between personal beliefs and social norms. The novel Are You There God? It's Me, Margaret by Judy Blume represents the struggles experienced by adolescents amidst social pressures and personal desires, as depicted through the main character, Margaret. This research applies literary criticism to discuss Margaret's journey in shaping her spiritual identity and anxiety about her physical development using Judith Butler's theory of gender performativity. Using a mimetic approach, the novel reflects social dynamics in 1970s America, including social pressures on gender roles and shifting patterns of religiosity. The results of this study show that Margaret's identity is formed through her interactions with society, influences from her family, and personal experiences. This research emphasizes that identity search is a dynamic process influenced by various internal and external factors.